Interrogating the Morality of Human Rights - Perry, Michael (Elgar Studies in Human Rights, 2023)
This forward-thinking book illustrates the complexities of the morality of human rights. Emphasising the role of human rights as the only true global political morality to arise since the Second World War, chapters explore its role as applied to often controversial issues, such as capital punishment, the exclusion of same-sex couples from civil marriage and criminal abortion bans.